Balance between oxidation and tribological behaviors at elevated temperatures of Hf1-xWxN films by optimizing W content. (January 2023) - Yu, Wei; Li, Hang; Li, Jianliang; Liu, Zhaoli; Huang, Jiewen; Kong, Jian; Wu, Qiujie; Shi, Yan; Zhang, Guichang; Xiong, Dangsheng
Abstract: Wear resistance and anti-oxidization are required for the binary transitional metal nitride coatings when they are applied as protective coating on cutting tools. The dope with other transitional metal elements is one of the effective strategies to enhance the wear resistance of binary transitional metal nitride coatings. In this study, Hf1-x Wx N ternary coatings with various W content were prepared by DC magnetron sputtering. The hardness, toughness and tribological properties of Hf1-x Wx N coatings varied with W doping amounts were investigated. The results show that the Hf1-x Wx N coatings with the x range of 0–1 maintain B1 structure (FCC single solid solution phase). High hardness (35.3 GPa) and enhanced toughness (3.5 MPa m 1/2 ) are obtained from Hf1-x Wx N coating with x = 0.73 (Hf0.27 W0.73 N). The friction coefficient and wear rate of Hf0.27 W0.73 N are as low as 0.38 and 2.48 × 10 −6 mm 3 /Nm at room temperature, while they are 0.42 and 8.12 × 10 −6 mm 3 /Nm at the temperature of 400 °C. The excellent friction and wear properties of Hf1-x Wx N coatings at elevated temperatures are mainly attributed to the enhanced mechanical properties and the lubrication of tungsten oxides (WO3 ). The balance between oxidation and tribological behaviors of Hf1-x Wx N coatings are achieved by optimizing W content. Highlights: Hf1-x Wx N films with x = 0–1 are FCC structure with single phase solid-solution. Hf0.27 W0.73 N film maintained the better mechanical properties (KIC 3.5 MPa m 1/2 ). The tribological properties of Hf1-x Wx N films at RT were controlled by the H/E. The lubrication WOx and B1 structure improved the film wear resistance at 400-600 °C. Low wear rate of 2.48 and 8.12 × 10 −6 mm 3 /Nm obtained at x = 0.73 under RT and 400 °C.